Molecular determinants of peri-apical targeting of inositol 1,4,5-trisphosphate receptor type 3 in cholangiocytes - Rodrigues M.A. (2023)
Fluid and bicarbonate secretion is a principal function of cholangiocytes, and impaired secretion results in cholestasis. Cholangiocyte secretion depends on peri-apical expression of the type 3 inositol trisphosphate receptor (ITPR3), and loss of this intracellular Ca2+ release channel is a final common event in most cholangiopathies. Here we investigated the mechanism by which ITPR3 localizes to the apical region to regulate secretion. Isolated bile duct units, primary mouse cholangiocytes, and polarized Madin-Darby canine kidney (MDCK) cells were examined using a combination of biochemical and fluorescence microscopy techniques to investigate the mechanism of ITPR3 targeting to the apical region. Apical localization of ITPR3 depended on the presence of intact lipid rafts as well as interactions with both caveolin 1 (CAV1) and myosin heavy chain 9 (MYH9). Chemical disruption of lipid rafts or knockdown of CAV1 or MYH9 redistributed ITPR3 away from the apical region. MYH9 interacted with the five c-terminal amino acids of the ITPR3 peptide. Disruption of lipid rafts impaired Ca2+ signaling, and absence of CAV1 impaired both Ca2+ signaling and fluid secretion. Conclusion: A cooperative mechanism involving MYH9, CAV1, and apical lipid rafts localize ITPR3 to the apical region to regulate Ca2+ signaling and secretion in cholangiocytes.